ON SIMILARITIES BETWEEN THE EARTH ROTATION AND TEMPERATURE CHANGES - Zotov, L. V. (Одеські астрономічні публікації, 2012)
Earths rotation reflects processes in the atmosphere, ocean, Earths interior. The similarities between the global temperature oscillations and Earths rotation speed changes are well known, but still are not explained. We also have found similarities between ~ 20-year temperature oscillations, Chandler excitation envelope and cycle of regression of the Moon orbital nodes. In this short article we want to attract attention to this fact.